Pengaruh Peranan Sikap, Norma Subjektif, dan Perceived Behavior Control Terhadap Niat Mengunjungi Kembali Studi Kasus pada Wisata Central Park Meikarta Cikarang - Afifah Putri Dwi Lestari; Wiji Safitri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to determine the effect of the role of attitudes, subjective norms and perceived behavior control on the intention to revisit Meikarta Central Park Cikarang. This study used a quantitative method with data collection techniques through distributing questionnaires. The sample in this study were 80 tourists who had visited Central Park Meikarta using the saturated sample method. The data analysis technique used is multiple linear regression using SmartPLS. The intention to revisit tourist attractions has a positive and significant effect on the variable role of tourist attitudes. Subjective norms have a positive and significant effect on the variable Intention to Revisit Tourist Attractions. Perceived behavior control (behavioral control) has a positive and significant effect on the variable Intention to Revisit Tourist Attractions. Furthermore, it is seen how much influence the role of attitudes, subjective norms and perceived behavior control has on the intention to revisit Meikarta Central Park Cikarang in hypothesis testing. From the results of multiple linear regression tests, it was found that attitude variables, subjective norms and perceived behavior control affect the intention to revisit tourist attractions. The collected data is processed using the regression test technique which is processed with the SmartPLS application. The concept of this research has been tested by instruments with validity and reliability results with decent results. Keywords: Attitude, Subjective Norm, Perceived Behavior Control, Revisit Intention